Android Snake Ladder on Triangle using TGT Learning Model to Increase Learning Motivation - Melania Eva Wulanningtyas; Yusup Davit Palma Putra; Ni Nyoman Triani; Nofica Andriyati (Hipotenusa : Journal of Mathematical Society, 2021)
The aims of this research were developing mathematics learning media based on android using Teams Games Tournament (TGT) learning type on triangle materials to improve learning motivation of class VII Junior High School students according to these validity, practical, and effective criterias through snake ladder game. The subject of this research were 28 students of class VII D SMP Negeri 1 Sedayu.  This research based on ADDIE developing model contains 5 steps: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of this research showed that mathematics learning media based on android using Teams Games Tournament (TGT) learning type on triangle materials to improve learning motivation of class VII Junior High School students was completed on: (1) validity aspect through material expert validation with score 64 and categorized very good in criteria also media expert validation with score 64 and categorized very good in criteria. (2) practical aspect through mathematics learning media based on android tested to 28 students with student response questionnaire score was 1.053 and categorized good in  criteria. (3) effectiveness aspect through increasing learning motivation students as much as 26% from 54% to 80%. So, it can be concluded that mathematics learning media based on android is appropriate for learning activity and beneficial to improve learning motivation students.